Pengaruh Kualitas Pelayanan, Harga, dan Lokasi terhadap Kepuasan Pelanggan pada Kohikato Coffee di Kota Depok - Hidayat, Rachmat; Putra, Suadi Sapta; Digdowiseiso, Kumba (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study was to see the effect of Service Quality, Price, and Location on Kohikato Coffee Customer Satisfaction in Depok City. This type of research uses primary data as data obtained directly by filling out questionnaires to 100 participants. The data analysis technique used in this research is multiple linear regression analysis and hypothesis testing using t-statistics which is processed using the SPSS system. The results of the study obtained a positive and insignificant effect between Service Quality (X1) on Customer Satisfaction (X2) Price has a positive and significant effect on Customer Satisfaction (X3) Location has a positive and significant effect on Customer Satisfaction. Overall, it shows that these variables have a positive and significant influence on customer satisfaction (Y).